Not all that clear cut: intraspecific morphological variability in Squalus blainville (Risso, 1827) and implications for identification of the species. (15th December 2015) - Bonello, Juan José; Bonnici, Leanne; Ferrari, Alice; Cariani, Alessia; Schembri, Patrick J.
Abstract : Of the three species of the genus Squalus that occur in the Mediterranean Sea, S. blainville and S. megalops are very difficult to distinguish. This study assesses the variability in morphological features that have been used to differentiate between these species. Squalus were collected from stations within the 25-nautical mile Fisheries Management Zone around the Maltese Islands; 349 specimens were dissected and categorized into male and female, mature and immature, and individuals were randomly selected from each category to make up a sample of 169 specimens. For each individual, total length and first dorsal fin parameters were measured, and morphology of denticles isolated from the laterodorsal area, of the upper and lower teeth and of the chondrocranium was analysed. The first dorsal spine was shorter that the fin base in 93% of the specimens, which is typical of S. megalops ; this character was not related to either gender or maturity. Chondrocrania with one lateral process (typical of S. blainville ) and two lateral processes (typical of S. megalops ) were present. Teeth from the same individuals showed morphological features that overlap between S. blainville and S. megalops . Both unicuspid (typical of S. megalops ) and tricuspid denticles (typical of S. blainville ) were observed on the same individuals. Twelve specimens (six having one and six having two lateral chondrocranial processes) were analysed genetically by sequencing of the mtDNA marker Cytochrome Oxidase Subunit I (COI). All resulted to be S. blainville showing that intraspecific variability in supposedly diagnostic morphological features is large enough to render these unreliable to tell apart these two species, especially in the field.